FAKTOR FAKTOR YANG MEMPENGARUHI KEBIJAKAN DEVIDEN PADA PERUSAHAAN INDUSTRI BARANG DAN KONSUMSI YANG TERDAFTAR DI BURSA EFEK INDONESIA - Saragih, Joana L.; Purba, Betniar; Simangunsong, Elisabeth (Jurnal Manajemen dan Bisnis, 2021)
This study aims to find out the extent of influence, profitability, liquidity, company size and leverage on dividend policy on industrial goods and consumption companies listed on the Indonesia Stock Exchange. The population in this study was 59 industrial companies of goods and consumption. Sampling techniques used is purposive sampling in accordance with the criteria that have been determined, so obtained samples 45 companies, with a research period of 3 years so that the total number of 45. The data analysis techniques used are multiple linear regression analysis and hypothesis testing using t test and F test with a significance rate of 5%. Partial test results (t test) show profitability has a positive and significant effect on dividend policy, liquidity has an insignificant positive effect on dividend policy, company size has insignificant positive effect and leverage negatively and significantly affects dividend policy. Simultaneous test results (test F) show that variable profitability, liquidity, company size and leverage together have a positive and significant effect on dividend policy in Goods and Consumption Industry companies listed on the Indonesia Stock Exchange (IDX).